Launching into a golden age: gears (mm parts) made by the deep X-ray LIG(A) process. (3rd November 2008) - Meyer, Pascal; Saile, Volker; Schulz, Joachim; Klein, Olaf; , Markus Arendt
For the fabrication of highly precise mm parts, different processes could be chosen. The performance criteria of any process are multiple; quality (to deliver to the customer what they expect) and price belongs to them. The LIGA fabrication technique meets the first point and in a near future, the second one as well. Why choose the direct LIGA technique and which performance can be achieved using this process? To answer these questions, we present two studies: prototype fabrication and tests of 900 µm and 1400 &181;m thick direct Nickel/Cobalt (Ni/Co) LIG(A) gears made for a market leader in miniaturised micro powertrains, and the fabrication of 180 µm thick direct gold (Au) gear wheels. The quality of the finished parts will be addressed. Furthermore, by taking these two cases as examples, we will present a simulation of future production using a fully automated fabrication line (FELIG).